(untitled) (Annals of Medical Research, 2021)
Aim: To report our experience with the renal biopsy/complications and histopathologic patterns of renal diseases according to their clinical presentation and to make the best disease management in the elderly patients. Material and Methods: Totally 136 patients were analyzed according to their renal biopsy histopathology, clinical diagnosis and biopsy related complications between 2006 and 2016.Results: Nephrotic syndrome (NS) and acute kidney injury (AKI) were the leading indications for renal biopsy. Totally 65 patients (47%) were diagnosed as NS and 60 patients (44%) were AKI. The most frequent histopathologic diagnosis was amyloidosis (30%). Membranous nephropathy (22%) was the second frequent histopathologic diagnosis. Amyloidosis (18.3%) was the leading cause of nephrotic syndrome and membranous nephropathy (17.6%) was the second most seen cause. Amyloidosis (11%) was the mostly seen histopathologic diagnosis of AKI. Back pain longer than 12 hours (10%) was the most common complication.Conclusion: According to our findings, renal disease of elderly differs from other age groups according to histopathologic distribution, early renal function loss and rapid progression to end stage renal disease. For an accurate early diagnosis and initiating specific treatment, renal biopsy should be performed on an individual basis without an increased risk for renal biopsy related complications.Keywords: Acute kidney injury; nephrotic syndrome; renal biopsy; elderly; renal histopathology.